Comparison Between the Fixation of Peritoneal Dialysis Catheters to the Peritoneal Wall and the Conventional Placement Technique: Clinical Experience and Follow‐Up of a New Implant Technique for Peritoneal Dialysis Catheters. Issue 4 (22nd November 2013) - Io, Hiroaki; Maeda, Kunimi; Sekiguchi, Yoshimi; Shimaoka, Tetsutaro; Aruga, Seiki; Nakata, Junichiro; Nakamoto, Hirotaka; Hotta, Yoko; Koyanagi, Ichiro; Inaba, Masanori; Kanda, Reo; Nakano, Takanori; et al.
Abstract Peritoneal dialysis (PD) catheters often become severely dislocated, which may lead to malfunction. With the aim of preventing this complication, we have developed a simple method of fixing the catheter downwards in the peritoneal cavity (fixation technique), a technique that does not require a laparoscope. Sixteen patients were implanted using the conventional placement technique and 25 patients were implanted using the fixation technique. The location of the catheter tip was classified from grade 1 (downward, normal) to 5 (dislocated). The frequency of dislocation (defined as the extended time and/or decrease in volume when draining the PD solution) was measured for both the fixation technique and conventional placement technique. There was a significant difference in grade between the fixation technique (2.72 ± 1.01) and conventional technique (3.92 ± 1.31). The time until first dislocation was significantly different between the fixation technique (59.3 ± 48.1 days) and conventional technique (8.8 ± 14.6 days). The time until any dislocation was significantly different between the fixation technique (69.2 ± 41.9 days) and conventional technique (12.9 ± 13.7 days). Complications were not significantly different between the fixation technique and conventional technique. The fixation technique appears to be simple, safe, and useful for preventing severe dislocation and for lengthening the time until dislocation in PD patients.